2017
DOI: 10.31018/jans.v9i1.1227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing dates and varieties on soybean performance in Vidarbha region of Maharashtra, India

Abstract: Soybean production is widely fluctuating in response to agro-environmental conditions year to year in Vidarbha region. Weather variations are the major determinants of soybean growth and yield. It is also important to study the response of suitable soybean varieties to varying weather parameters. So a field investigation was carried out to study the crop weather relationship of soybean and to optimize the sowing date with different soybean varieties. The results revealed that soybean crop sown up to 27 th MW a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This phenomenon contributed to the observed increase in LAI. These findings resonate with the results reported by Vyas and khandwe (2014) [38] and Nath et al (2017) [23] . Planting geometry of 30 cm × 10 cm exhibited the highest leaf area index (4.45), followed by 37.5 cm × 10 cm (3.45) and 45 cm × 10 cm (2.53).…”
Section: Leaf Area Indexsupporting
confidence: 93%
“…This phenomenon contributed to the observed increase in LAI. These findings resonate with the results reported by Vyas and khandwe (2014) [38] and Nath et al (2017) [23] . Planting geometry of 30 cm × 10 cm exhibited the highest leaf area index (4.45), followed by 37.5 cm × 10 cm (3.45) and 45 cm × 10 cm (2.53).…”
Section: Leaf Area Indexsupporting
confidence: 93%
“…The highest above ground dry biomass (3010.2kg ha -1 ) was recorded at inter row spacing of 30cm and the lowest biomass (2773.1kg ha -1 ) was recorded at inter row spacing of 60cm (Table 5). In line with this finding, Nath et al (2017) indicated dry matter weight is attributed to their genetic potential rather than the effect of external weather parameters in soybean. According to Vanlauwe et al(2003) high biomass of soybean was obtained in late maturing varieties than in the early maturing.…”
Section: Hundred Grains Weightsupporting
confidence: 68%
“…And in Keyvan and Kobraee (2012) study also obtained highly significant variation was observed soybean varieties in response to grain yield. Nath et al (2017) described as seed yield was highly influenced by varieties.…”
Section: Hundred Grains Weightmentioning
confidence: 99%
“…Further, the least biomass accumulation (4.86 g plant -1 ) was recorded in 3 Dec (D5) sowing. The favourable weather conditions have positive influence on biomass accumulation was reported by several researchers [10,11,12,13]. Further Kumar et al [14] reported that early sowing provides long vegetative and reproductive growth periods thereby, facilitating the crop to produce more biomass and late sowings may produce lower biomass and yield due to a variety of reasons including shortening of growth period, less accumulation of photosynthetically active radiation and less number of heat units and helio-thermal units…”
Section: Biomass (G Plant -1 )mentioning
confidence: 94%